The role of Clostridium butyricum and its metabolites in modulating gut mucosal immunity: implications for viral infections and inflammatory diseases - Qian, Shaoju; Li, Siyu; Ye, Keyan; Lu, Shuao; Sha, Xiaoming; Zhang, Danqiong; Xu, Zhishan; Song, Xiangfeng; Li, Ruixue (Frontiers in Immunology, 2026)
With global viral emergence and increasing antiviral resistance, there is an urgent need for innovative immunomodulatory strategies. Gut microbiota modulation has gained attention as a promising therapeutic approach. Clostridium butyricum (C. butyricum) plays a pivotal role in shaping microbial composition, preserving intestinal barrier integrity, and enhancing mucosal immunity. Its major metabolites, short-chain fatty acids (SCFAs), further strengthen mucosal defenses and exert antiviral and anti-inflammatory effects. This review proposes a unified “gut-centric hypothesis” that intestinal barrier integrity, microbial homeostasis, and mucosal immune balance collectively determine the host’s resilience to viral invasion and inflammation. The collective findings delineate a mechanistic axis whereby C. butyricum orchestrates antiviral and anti-inflammatory immunity through the induction of type I/III interferons, modulation of inflammasome signaling, and expansion of regulatory immune populations, reinforcing its therapeutic promise. This review provides a new conceptual framework linking probiotic action to antiviral immunity, identifying C. butyricum as a potential next-generation microbial therapeutic for viral and inflammatory diseases.